2022
DOI: 10.1096/fj.202200163r
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of inhibiting necroptosis on gentamicin‐induced nephrotoxicity

Abstract: Necroptosis is defined as a novel programmed cell necrosis that is mediated by receptor interacting serine-threonine protein kinase 1 (RIPK1) and other related signals. Necrosis, apoptosis and inflammation are commonly considered as the leading mechanism in acute kidney injury (AKI) induced by gentamicin (GEN), which is a useful antibiotic for treating the infection of Gram-negative bacterial.However, the necroptosis in the pathogenesis of GEN-induced AKI is unknown.In this study, to investigate the process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Nec-1 is an inhibitor of receptor-interacting protein 1 kinase, which inhibits RIPK1 kinase activity and reduces LN inflammation [ 36 , 37 ]. As shown in Figure 4 C, PMA can promote NET production.…”
Section: Resultsmentioning
confidence: 99%
“…Nec-1 is an inhibitor of receptor-interacting protein 1 kinase, which inhibits RIPK1 kinase activity and reduces LN inflammation [ 36 , 37 ]. As shown in Figure 4 C, PMA can promote NET production.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with that reported in our previous study, the current study was performed in two more typical and common AKI models. Our study focused on the specific mechanism and site of action of RIPK3 in the necrosis pathway in the AKI models, whereas the previous study had demonstrated the effectiveness of Cpd‐42 in various AKI models from a different aspect (Hu et al, 2022). In this study, we used two in vitro models—cisplatin‐ and H/R‐induced renal cell injury—to determine whether Cpd‐42 exerts renoprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…The GEN group was added with different concentrations of GEN (0, 0.5, 1, 2, 4, 8, 16, 32, and 64 mM) and the GEN + EG group added the same concentrations of GEN and EG (25 μM). Finally, the turbidity of the two groups was compared after incubation for 24 H at 37 °C [ 39 ].…”
Section: Methodsmentioning
confidence: 99%